Nano DAP augments productivity, phosphorus use efficiency, and profitability of spring wheat - Kadapa Sreenivasa Reddy; Yashbir Singh Shivay; Dinesh Kumar; Binaya Kumar Parida; Ramakrishna Bora; Rohit Bapurao Borate; Kajal Das; Sunil Mandi; Somanath Nayak; Kirttiranjan Baral; Gunturi Alekhya (Scientific Reports)
Abstract Agriculture is undergoing a transformation through innovations like nano fertilizers, which offer the potential to enhance productivity and sustainability. This study aimed to evaluate the effectiveness of nano DAP to improve growth, yield attributes, nutrient uptake, and economic viability in wheat (Triticum aestivum L.) cultivation. A two-year field experiment during the rabi seasons of (2022–23, 2023-2024) was conducted at the ICAR-Indian Agricultural Research Institute, New Delhi, India, using a randomized complete block design with ten treatments. These included a control (zero P), 50%, 75%, and 100% of the recommended dose of phosphorus (RDP), with or without nano DAP sprays (2.5 ml and 5 ml L−1), replicated three times. Results demonstrated that the application of 100% RDP combined with two foliar sprays of nano DAP significantly increased grain yield by 34.8% and 14.7% in the 2022–2023 and 2023–2024 seasons, respectively, compared to the control. However, in 2022-23, P50 + nano2.5 ml L−1 resulted in a 13.7% reduction in yields, while P50 + nano5 ml L−1 showed a 7.8% decrease compared to P100. In 2023-24, both treatments achieved yields comparable to P100. Similarly, P75 + nano recorded yields on par with P100. Additionally, grain phosphorus (P) and nitrogen (N) uptake, showed substantial increases of 69.9% and 42.2% for P, and 54.2% and 26.7% for N in P100 across the two seasons, compared to control. Economic analysis revealed higher net returns of US $ 1,022.30 and US $ 1,248.90 ha−1 year−1 in 2022–2023 and 2023–2024, respectively. Reducing the P application to 75% RDP with two foliar sprays of nano DAP (5 ml L−1) resulted in wheat yields of 4.25 t ha−1 and 6.04 t ha−1 in 2022–2023 and 2023–2024, respectively, which were statistically comparable to the yields achieved with 100% RDP. This treatment also improved N uptake (84.2, 125.0 kg ha−1), P uptake (20.4, 24.2 kg ha−1), and net returns (US $ 958.60, US $ 1,197.10 ha−1 year−1) during 2022–23 and 2023–24, respectively. Thus, demonstrating its potential as an economically viable and environmentally sustainable alternative to conventional P100 application.